University Planning Forums Proceedings of the Seminar on Educated Unemployed Held at Trivandrum - Planning Commission (Planning Commission, 1956)
The problem of unemployment among the educated in the country is not of recent origin. It has been in the forefront of the country’s problems during the last three decades. The enquiries of certain official committees set up earlier in Madras, Bombay, Travancore-Cochin, U.P. and the Punjab revealed an excess of educated persons over employment openings suited to their qualifications and preferences. During the period of the second World War. The problem was solved by the increasing tempo of economic activity; but after the War the situation took a turn for the worse. The unemployment situation assumed serious proportions by the time the First Plan was half way through. It was felt more acutely in urban areas where the educated without jobs were the main sufferers.
Government of India Planning Commission